I Want to Participate—Communities of Practice in Foraging and Gardening Projects as a Contribution to Social and Cultural Sustainability in Early Childhood Education - Bergan, Veronica; Krempig, Inger Wallem; Utsi, Tove Aagnes; Bøe, Kari Wallem (Sustainability, 2021)
Learning and development in early childhood is highly dependent on social interaction and exploration through continuous encounters with the real world. Foraging and gardening are outdoor pedagogical practices that have relevance to education for sustainability. Previous work suggests that engagement in such activities can be characterized by the concept “community of practice” (CoP). In this paper, we explore how characteristics of the CoP can be recognized in foraging and gardening projects performed in the Arctic region of Norway, and we discuss how these activities can contribute to social and cultural aspects of sustainability. Data collection included focus group interviews with kindergarten staff (teachers and assistants) and videos taken of foraging and gardening activities with the children. Our data indicate that the hallmarks of CoP, domain, community, and practice, are strongly recognized in these projects through increased interest, social interaction, and agency for learning. This mutual engagement and participation in the CoPs for foraging and gardening connect both staff and children to local food heritage and culture for a sustainable future.